On mind-wandering : could mind-wandering be intentional? - Telli, Büşra (My University, 2023)
Zihin gezinmesi, son zamanların felsefi açıdan en ilgi çeken konularındandır. Bu tezde, benim cevaplamaya çalışacağım felsefi sorular ise şu şekildedir: Zihin gezinmesi pasif ya da aktif bir mental olgu mudur? Zihin gezinmesi süresince, zihinsel özerklik sağlanabilir mi? Zihin gezinmesi istemli olabilir mi? Benim cevabım zihin gezinmesinin aktif olduğu ve bu sebeple de zihinsel özerkliğin sağlanabileceği doğrultusundadır. Eğer ki zihin gezinmesi pasif bir zihinsel süreç ise ve zihin gezinmesi uyanık olarak geçirdiğimiz zamanın çoğunu kaplamaktaysa, hayatımızın büyük bir kısmını zihinsel özerklik olmadan geçirdiğimiz sonucu çıkarılabilir. Bu sepeble, Metzinger’in öne sürdüğü zihin gezinmesinin pasif olduğu görüşünü eleştirecek ve Carruthers’in görüşünü destekleyeceğim. Carruthers, zihin gezinmesinin aktif bir zihinsel süreç olduğunu savunmaktadır. Üçüncü sorudaki istemlilik ile alakalı kısımda ise, istemli zihin gezinmesi kavramını ele alan görüşleri inceleyeceğim. Seli ve arkadaşları ve Irving istemli zihin gezinmesini, zihin gezinmesinin aktif ve/ veya pasif olma durumu ile istemlilik kavramını ilişkilendirerek açıklamaktadırlar. Benim eleştirdiğim kısım ise, zihin gezinmesinin istemli ve istemsiz şekilde sınıflandırılarak tanımlanamayacağıdır. Çünkü zihinsel gezinmenin istemli ya da istemsiz olması, zihinsel gezinmenin özneye nasıl gözüktüğüyle alakalıdır.

While the phenomenon of mind-wandering is broadly studied in psychology, the need to better understand mind-wandering as a mental episode that affects our mental lives led philosophers to focus on mind-wandering as well. In this thesis, I will try to answer the following questions. Is mind-wandering an active or passive mode of thought? Do we have mental agency during mind-wandering? Can mind-wandering be intentional? My position is that if mind-wandering is active, we can have mental agency during a mind-wandering episode. If we have mental agency, we can have mental autonomy over that episode. I propose that it is important to accept mind-wandering as active due to its pervasiveness. If mind-wandering is passive, that means we do not have mental agency for nearly half of our wakeful lives. Thus, I will criticize Metzinger’s view on the passivity of mind-wandering and try to support my proposal with Carruthers’ view on mind-wandering, which is active and purposeful. For the intentionality part, I will discuss the approaches regarding the connection between intentionality and the active/ passive nature of mind-wandering (Seli et al., 2018; Irving, 2021). I find both of their approaches of intentional mind-wandering problematic in terms of how they make a connection between intentionality and passivity. If we need to make a connection, then I suggest that we should make this connection through propositional meta-awareness. Maybe what has been called intentional mind-wandering in their research is mind-wandering with propositional meta-awareness. Thus, my opinion is that being intentional or unintentional should not be used as a defining characteristic of mind-wandering because being intentional or unintentional has to do with how mind-wandering appears to the subject. It is not necessarily an intrinsic property of the mind-wandering episode itself.
Zihin gezinmesi üzerine : istemli zihin gezinmesi mümkün müdür?
Keywords: Beyin; Biliş; Brain; Cognition; Düşünce ve düşünme; Intentional mind-wandering; İstemli zihin gezinmesi; Mental action; Mental agency; Meta-awareness; Thought and thinking; Zihinsel aksiyon; Zihinsel farkındalık; Zihinsel özerklik